2004
DOI: 10.1136/bjsm.2003.005272
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and magnetic resonance imaging features of cricket bowler’s side strain

Abstract: The clinical features of 10 cases of lateral trunk muscle injury in first class cricket pace bowlers are described. Typically the injury occurs during a single delivery, is associated with considerable pain, and prevents the bowler from continuing. The clinical picture is typical of a muscular or musculotendinous injury. The most consistent clinical tests were focal tenderness on palpation and pain with resisted side flexion towards the painful side. The magnetic resonance image in 70% of cases was consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 3 publications
0
35
0
1
Order By: Relevance
“…Investigations of side strain in cricket bowlers using MRI found that the injury consistently occurred on the non-bowling side and tended to affect abdominal muscles (IO, external oblique and TrA muscles) rather than the QL muscle 39. This could suggest that the asymmetrical muscular demands of the repetitive bowling action creates hypertrophy in the torque-producing muscles of trunk rotation and side flexion 40.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of side strain in cricket bowlers using MRI found that the injury consistently occurred on the non-bowling side and tended to affect abdominal muscles (IO, external oblique and TrA muscles) rather than the QL muscle 39. This could suggest that the asymmetrical muscular demands of the repetitive bowling action creates hypertrophy in the torque-producing muscles of trunk rotation and side flexion 40.…”
Section: Discussionmentioning
confidence: 99%
“…Patient recovery is usually achieved through a combination of rest, non-steroidal anti-inflammatory drugs, and physiotherapy, although the length of time taken would appear to vary considerably. 4 In both these two patients, conservative measures, including physiotherapy, steroid injection, and altering their bowling action, failed to alleviate symptoms. Surgical resection was the only remaining treatment option.…”
Section: But the Mechanical Factors Involved In A Bowling Action Can mentioning
confidence: 96%
“…The injury that has consistently accounted for the most lost playing time is lower back stress fracture (Orchard et al, 2006, Newman, 2003, Ranson et al, 2008a. Side strains, (tear of the abdominal oblique muscles) (Humphries and Jamison, 2004) and repetitive micro-trauma injuries to the knee, leg and ankle are also relatively prevalent, particularly on the side of the body opposite to the bowling arm.…”
Section: Introductionmentioning
confidence: 99%